A Case of Childhood Hyperthyroidism - Daniel Hardjadinata; Gunadi Santosa; R. H. Sardjito (Paediatrica Indonesiana, 1984)
An unusual case of hyperthyroidism in a 4 years old girl is presented. The pathogenesis of this disease is still uncertain, but several possible pathogenesis are described. The diagnosis is rarely difficult if the clinical manifestations are characteristic, but these signs and symptoms are usually found in adults and older children. Several differential diagnosis are also considered and the treatment and prognosis discussed.